DEVELOPMENT AND ADJUSTMENT OF COMPLEX HYDRAULIC DRIVE WITH PLEATING MACHINE MECHANISMS - KOROTYCH , OLHA; POLISHHUK, ANDRIJ; MARCHENKO, MAKSYM; ZOLOTENKO, ELLA; MYKHAILOVSKY, YURIY (Herald of Khmelnytskyi National University. Technical sciences, 2024)
As a result of the analysis of the constructions of technological machines of light industry and direct pleating equipment, as well as their drives, identified shortcomings and advantages, the authors developed a complex hydraulic drive of a pleating machine, which includes a means of distributing the movement of the working fluid to the executive mechanisms, connected to the pumping unit and hydraulic cylinders of executive mechanisms. The means of distributing the movement of the working fluid to the executive mechanisms (hydraulic distributor) is an original design development in relation to the technological process and the cyclogram of the pleating machine of the knife-roll type. The three main executive mechanisms work cyclically in series-parallel in different phases. It is possible to adjust the parameters of pleats (their depth and width) by adjusting the range of motion of the pistons of the hydraulic cylinders. According to the developed schemes, a detailed description of the structure of the new hydraulic distributor and coordination of the operation of the complex hydraulic drive with the mechanisms of the pleating machine is presented. The hydraulic distributor of the new design can perform both the distribution and control function of distributing the working fluid simultaneously to three hydraulic motors of the executive mechanisms according to the cycle schedule of the pleating machine and can replace controlled automatic devices. As a result of reducing the number of parts in a pleating machine with a developed complex hydraulic drive, its design and manufacturing technology are simplified in comparison with electromechanical pleating machines due to the absence of the main shaft and mechanical gears that convert and transmit movements from the electric motor to the actuators. The constructive method of developing a hydraulic distributor of a complex hydraulic drive of a pleating machine can be used for other machines that have mechanisms that work in different phases of the cyclogram.